A study on persuasive system features to help kids with speech delay problem - Hang, Wei Hen (2024)
Speech delay in children is a prevalent concern, often necessitating early intervention for optimal outcomes. Traditional therapy methods conducted solely by speech-language pathologists can be costly and inaccessible, prompting the need for alternative solutions. This research investigates the effectiveness of persuasive systems, particularly mobile applications, in addressing speech delay issues in children. A quantitative research approach was employed, utilizing a structured questionnaire distributed to parents of children with speech delay. Purposive sampling targeted this specific demographic to gain insights into the efficacy of mobile app features for speech delay therapy. Data collection involved four phases: literature review, questionnaire design, distribution, and analysis. Statistical methods, including regression analysis and t-tests, were employed to evaluate the effectiveness of persuasive system elements. Analysis of the data revealed significant positive correlations between various aspects of language development, including pronunciation, comprehension, expressive vocabulary, and articulation skills. Descriptive statistics indicated overall agreement among respondents regarding the effectiveness of different therapeutic methods incorporated into mobile applications. The findings suggest that mobile applications can serve as valuable tools in speech delay therapy, offering cost-effective, accessible, and engaging interventions for children. The study contributes insights into the design and implementation of persuasive systems tailored to address speech delay issues, benefiting both parents and society by promoting early intervention and enhancing developmental outcomes. This research underscores the potential of persuasive systems, particularly mobile applications, in augmenting traditional speech delay therapy methods. By leveraging technology to deliver tailored interventions, such systems can facilitate early detection, intervention, and ongoing support for children with speech delay, ultimately improving their communication abilities and quality of life.